2011
DOI: 10.1016/j.jaac.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Child Psychopathic Traits Moderate Relationships Between Parental Affect and Child Aggression

Abstract: Objective Previous studies show that children with psychopathic traits may be less responsive to parenting. While harsh/inconsistent parenting is associated with increased problem behaviors in children low on psychopathic traits, children high on psychopathic traits show consistently high levels of problem behavior regardless of negative parenting. Moderating effects of child psychopathy on positive dimensions of parenting have not been explored. Method We applied multi-level regression models to test for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 63 publications
(66 reference statements)
2
26
0
6
Order By: Relevance
“…More notable contrary findings include the observation that caregiving quality predicts CU stability (P. J. Frick, Kimonis, Dandreaux, & Farell, 2003); parental warmth may have a stronger association with problem behavior in children with elevated levels of CU traits (Kroneman, Hipwell, Loeber, Koot, & Pardini, 2011); and children with CU traits may be more sensitive to coercive parenting for proactive aggression (Yeh et al, 2011). These findings are significant in raising an alternative hypothesis that children with CU traits may, in certain circumstances, show greater sensitivity or responsiveness to caregiving.…”
Section: Observational and Experimental Findingsmentioning
confidence: 93%
See 1 more Smart Citation
“…More notable contrary findings include the observation that caregiving quality predicts CU stability (P. J. Frick, Kimonis, Dandreaux, & Farell, 2003); parental warmth may have a stronger association with problem behavior in children with elevated levels of CU traits (Kroneman, Hipwell, Loeber, Koot, & Pardini, 2011); and children with CU traits may be more sensitive to coercive parenting for proactive aggression (Yeh et al, 2011). These findings are significant in raising an alternative hypothesis that children with CU traits may, in certain circumstances, show greater sensitivity or responsiveness to caregiving.…”
Section: Observational and Experimental Findingsmentioning
confidence: 93%
“…More direct evidence derives from studies showing that CU traits moderate associations between a range of parenting dimensions and behavioral adjustment. For example, in a sample of 9-10 year-olds, Yeh and colleagues (Yeh, Chen, Raine, Baker, & Jacobson, 2011) found that children's reporting of both positive and negative parenting were more strongly associated with self-reported reactive aggression in children with low versus high levels of psychopathic traits. A study of young clinic-referred children (Pasalich, Dadds, Hawes, & Brennan, 2011) found that coercive parenting was more strongly associated with conduct problems in children with low compared with elevated levels of CU; other studies suggest that disciplinary practices may be more weakly associated with behavioral problems in children with elevated CU traits (Oxford, Cavell, & Hughes, 2003;Wootton, Frick, Shelton, & Silverthorn, 1997).…”
Section: Observational and Experimental Findingsmentioning
confidence: 99%
“…En primer término, los hallazgos indicaron que la conducta moderada de orden oposicionista desafiante es, en alto grado, consecuencia de la práctica negativa denominada disciplina inconsistente, tal como Yeh et al (2011) habían demostrado. En específico, que los niños hagan berrinches, discutan con adultos, se opongan a obedecer, molesten a las personas, culpen a otros por lo sociales limitadas o, dicho de manera más operacional, la ocurrencia de conductas problemáticas infantilesdesde moderadas hasta severas; para ello puede ser viable considerar la promoción de prácticas positivas de crianza, a fin de prevenir el comportamiento antisocial en la adolescencia o el consumo de drogas en etapas posteriores de la vida.…”
Section: Discusión Y Conclusionesunclassified
“…Aunque, en general, se ha planteado que los problemas de conducta parecen ser resultado de una disciplina rígida, inconsistente y coercitiva (Yeh, Chen, Raine, Baker, & Jacobson, 2011). Clark y Frick (2016), McDonald, Dodson, Rosenfield y Jouriles (2011), y Morales et al (2017) han mencionado que las prácticas de crianza se clasifican en positivas y negativas.…”
Section: Introductionunclassified
“…La literatura tradicional indica que la disciplina rígida, inconsistente, coercitiva (Barker, Oliver, Viding, Salekin, & Maughan, 2011;Yeh, Chen, Raine, Baker, & Jacobson, 2011) y los estilos de crianza de baja calidez (Kroneman, Hipwell, Loeber, Koot, & Pardini, 2011) (Dadds, Allen, et al, 2012) tanto con padres como con madres, independientemente del tipo de problemas de conducta que presentan (Dadds, Jambrak, Pasalich, Hawes, & Brennan, 2011). Los estudios dirigidos a comprender las diferencias entre los estilos de crianza conforme la severidad o tipos de problemas de conducta, pueden ayudar a construir los modelos explicativos del desarrollo de la conducta problemática infantil.…”
unclassified